The Suku Laut View of the Settlement Program in Lingga Regency - Elsera, Marisa; Wisadirana, Darsono; Kuswandoro, Wawan Edi; Chawa, Anif Fatma; Anggaunitakiranantika, Anggaunitakiranantika; Syafitri, Rahma (Jurnal Sosiologi Andalas, 2024)
Abstract: This research analyses the views of the Suku Laut on development policies that have resettled them from a nomadic life at sea to a sedentary life on land. The top-down development approach often does not actively involve the Suku Laut, leading to various responses. The research method used was descriptive qualitative, with in-depth interviews and observations of 10 informants of the Sea Tribe in the Riau Islands. Peter L. Berger's social construction theory analyzed how social change occurs through externalization, objectivation, and internalization. Based on the research results, two main views of the Suku Laut towards development policies resulted from social construction. Both views reflect the complex dynamics of identity, access, and interaction with the new social environment. Firstly, some felt that development was not inclusive because it threatened their cultural identity, access to resources, and lack of involvement in decision-making. Secondly, some Suku Laut consider the policy sufficient to fulfill their basic needs, such as education, health, and protection from extreme weather. These different views are influenced by their living patterns, whether they are still nomadic, settled on the coast, or land. This article shows that the change from nomadic to settled life results from social construction created through the interaction of the Suku Laut with external society